Editorial: Research on emotion and learning: contributions from Latin America - Hurtado Parrado, Camilo (2020)
Latin America has increased its share of world scientific publications by nearly twofold during the last two decades (approximately from 2 to 4%). Despite this positive trend, the scholarly impact of scientific research produced in the region - measured in terms of citation rate - remains low. Two interrelated factors that contribute to this situation is that most research groups tend to work in isolation or in local sporadic collaboration, and results are often published in journals that are not indexed in major citation databases (e.g., SCOPUS, or Web of Science). Ultimately, part of Latin American high-quality research seems to remain hidden from the rest of the world. Over the last decades, an important number of Latin American scientists have developed fruitful research agendas on questions on learning and emotion, focusing on basic and/or translational research with humans and other animal models, and implementing diverse methodologies. Notwithstanding the important contributions of these research programs, Latin American research on emotion and learning has followed the overall trend of other research fields throughout the region; namely, remaining partially hidden from the large scientific community of the world. This Research Topic aimed to engage researchers from Latin America to share their empirical and conceptual work on learning and emotion. Ultimately, this effort was expected to strengthen and integrate our regional community of experts, enhance global networking, and establish new challenges and developments for future investigation.